Introduction to the Second Special Issue: Acute, Intensive, and Residential Services. Issue 4 (2nd October 2022) - Thompson, Alysha D.; Leffler, Jarrod; Vaughn, Aaron J.
ABSTRACT: This second special issue of Evidence Based Practice in Child and Adolescent Mental Health will focus on Acute, Intensive, and Residential Services (AIRS) for youth. Despite recent increases in AIRS research, there remains a shortage of applying, evaluating, and developing evidence-based treatments (EBTs) in these settings. In addition, since the publication of our first special issue, the American Academy of Pediatrics (AAP), Children's Hospital Alliance (CHA), and American Academy of Child and Adolescent Psychiatry (AACAP) have issued a joint statement declaring the state of youth mental illness to be a national crisis, worsened by the COVID-19 pandemic (American Academy of Pediatrics, Children's Hospital Association, & American Academy of Child and Adolescent Psychiatrists [AAP, CHA, & AACAP], 2021). The introduction to the special issue will highlight work being done in AIRS settings for youth around the country.